1999
DOI: 10.1097/00005537-199907000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Function and Histologic Appearance in the Injured Glottis With Topical Mitomycin‐C

Abstract: This study demonstrates functional preservation and improved histological appearance of the injured glottis after a single treatment with topical mitomycin-C. Potential applications of these findings include prophylactic use of topical mitomycin-C on glottic insults that commonly progress from granulation tissue formation to scarring and decreased vocal fold function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 15 publications
1
63
0
3
Order By: Relevance
“…Gray, Tritle (2003) 8 , noted that MMC showed a greater effect in delaying scarring, when applied right before and after damaging the tissue, suggesting that there might be an adequate time interval between the lesion formation and the application time for obtaining the proper effect. Spector et al (1999) 9 , showed significant reduction in granuloma formation and improvement in the crico-arythenoid mobility when using CO 2 laser with topical MMC. Garrett et al (2001) 1 showed that total collagen decrease was fixed with the use of topical MMC.…”
Section: Discussionmentioning
confidence: 96%
“…Gray, Tritle (2003) 8 , noted that MMC showed a greater effect in delaying scarring, when applied right before and after damaging the tissue, suggesting that there might be an adequate time interval between the lesion formation and the application time for obtaining the proper effect. Spector et al (1999) 9 , showed significant reduction in granuloma formation and improvement in the crico-arythenoid mobility when using CO 2 laser with topical MMC. Garrett et al (2001) 1 showed that total collagen decrease was fixed with the use of topical MMC.…”
Section: Discussionmentioning
confidence: 96%
“…Trabalhos in vitro demonstram sua capacidade de inibição de fibroblastos 4 e esta característica determinou, após estudos experimentais em animais 5,6 , o início de seu uso em oftalmologia para o controle da recidiva nas cirurgias do pterígeo e do glaucoma 7,8,9 . Raros trabalhos na área da otorrinolaringologia foram feitos, apenas experimentalmente, em animais, para observar cicatrizações de traumas laríngeos induzidos [10][11][12][13][14] , assim como para retardar a cicatrização de paracenteses da membrana timpânica, o que poderia ser usado como alternativa para a cirurgia de colocação de tubos de ventilação [15][16][17][18] . Um trabalho apresenta a possibilidade de seu uso tópico, no saco endolinfático, para tratamento da doença de Ménière 19 .…”
Section: Introductionunclassified
“…Since 1997, the otolaryngologists were interested in using mitomycin in situations that required scars' treatment on structural tubes as larynx, trachea and nose, reporting success in these applications 20,21,9,22 .…”
Section: Discussionmentioning
confidence: 99%